Dynamics of a Diffusive Predator-Prey Model with Allee Effect on Predator - Xiaoqin Wang; Yongli Cai; Huihai Ma (Discrete Dynamics in Nature and Society)
The reaction-diffusion Holling-Tanner prey-predator model considering the Allee effect on predator, under zero-flux boundary conditions, is discussed. Some properties of the solutions, such as dissipation and persistence, are obtained. Local and global stability of the positive equilibrium and Turing instability are studied. With the help of the numerical simulations, the rich Turing patterns, including holes, stripes, and spots patterns, are obtained.